Association of ionospheric storms and substorms of Global Electron Content with proxy AE index. Issue 7 (1st October 2015) - Yenen, S.D.; Gulyaeva, T.L.; Arikan, F.; Arikan, O.
Highlights The variability of GEC is related to smoothed and normalized AE index through a polynomial model. Storm onset time is determined using the IMF-B, dB/dt, IMF-Bz and smoothed AE variation. Proxy AE index can be used for identifying the effects of storms in auroral regions.